Prion Diseases - Takada, Leonel T.; Geschwind, Michael D. (Seminars in Neurology, 2013)
Prion diseases are a group of diseases caused by abnormally conformed infectious proteins, called prions. They can be sporadic (Jakob-Creutzfeldt disease [JCD]), genetic (genetic JCD, Gerstmann-Sträussler-Scheinker, and familial fatal insomnia), or acquired (kuru, variant JCD, and iatrogenic JCD). The clinical features associated with each form of prion disease, the neuroimaging findings, cerebrospinal fluid markers, and neuropathological findings are reviewed. Sporadic JCD is the most common form of human prion disease, and will be discussed in detail. Genetic prion diseases are caused by mutations in the prion-related protein gene (PRNP), and they are classified based on the mutation, clinical phenotype, and neuropathological features. Acquired prion diseases fortunately are becoming rarer, as awareness of transmission risk has led to implementation of measures to prevent such occurrences, but continued surveillance is necessary to prevent future cases. Treatment and management issues are also discussed.
Keywords: prion diseases; Creutzfeldt-Jakob disease; Gerstmann-Sträussler-Scheinker disease; familial fatal insomnia; rapidly progressive dementia